Analisis Dampak Kebijakan Moneter Terhadap Pertumbuhan Aset Bank Syariah - Sakinah Mulia Diny; Renny Oktafia (ISLAMIC BUSINESS and FINANCE, 2025)
The monetary policy plays a significant role in shaping economic conditions, including in the Islamic banking sector. This article aims to analyze the impact of monetary policy on the growth of Islamic banks in the current economic context. The study employs a qualitative method based on previous data, other articles, books, and internet sources to support the research. The analysis results indicate that monetary policy has a significant impact on the profitability of Islamic banks. Changes in interest rates, liquidity, inflation, and other related monetary policy variables have correlations that can influence profit margins and overall bank performance. This research provides insights for financial practitioners, regulators, and academics to understand how monetary policy can affect the stability and growth of Islamic banks. The study also includes adjustments to risk and financial management strategies to address potential changes in market conditions.Monetary Policy, Islamic Bank, Interest Rates